2018
DOI: 10.1159/000491566
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcome of Twice-Weekly Hemodialysis Patients with Long-Term Dialysis Vintage

Abstract: Background/Aims: Twice-weekly hemodialysis(HD) is prevalent in the developing countries, scarce data are available for this treatment in patients with long-term dialysis vintage. Methods: 106 patients with more than 5 years HD vintage undergoing twice-weekly HD or thrice-weekly HD in a hemodialysis center in Shanghai between December 1, 2013 and December 31, 2013 were enrolled into the cohort study with 3 years follow-up. Kaplan–Meier analysis and Cox proportional hazards models were used to compare patient su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 25 publications
2
19
0
Order By: Relevance
“…Of note, despite that twice-weekly HD tended to have worse hydration status than that of thrice-weekly HD, we found that the two groups had similar survival, this result was consistent with many previous studies [ 6 , 7 , 28 ]. Several factors might contribute to the result: Firstly, a relatively higher rate of patients with maintained urine output in twice-weekly HD group would favor this treatment; secondly, a higher SpKt/V,a longer HD session time and a shorter HD vintage also benefited twice-weekly HD in the study.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Of note, despite that twice-weekly HD tended to have worse hydration status than that of thrice-weekly HD, we found that the two groups had similar survival, this result was consistent with many previous studies [ 6 , 7 , 28 ]. Several factors might contribute to the result: Firstly, a relatively higher rate of patients with maintained urine output in twice-weekly HD group would favor this treatment; secondly, a higher SpKt/V,a longer HD session time and a shorter HD vintage also benefited twice-weekly HD in the study.…”
Section: Discussionsupporting
confidence: 93%
“…The 2006 K-DOQI guidelines recommended that the target of spKt/ V at least 2.0 for twice-weekly HD patients with residual native kidney urea clearance (Kr) more than 2 mL/min/ 1.73 m 2 , and it is not appropriate for those with Kr less than 2 mL/min/1.73 m 2 selecting this treatment model [4]. Nevertheless, due to financial constraints and resources limitations, it is not uncommon for patients without residual kidney function (RKF) undergoing twice-weekly HD [5][6][7], and some patients have been reported having treatment with twice-weekly HD for more than 20 years HD vintage [7].…”
Section: Introductionmentioning
confidence: 99%
“…Though there were a few studies that investigated the costs of dialysis treatments in low–middle income countries, there is a lack of studies conducted among hemodialysis patients in Vietnam [ 19 , 20 ]. In addition, it remains difficult for clinicians to provide individualized care based on socio-demographic characteristics as well as clinical and laboratory parameters [ 21 ]. It has been suggested that factors associated with a decline in HRQOL during renal progression should be investigated [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, studies suggest that it is possible to try initiating twice-weekly HD in patients who retain significant residual kidney function. In our meta-analysis of three such studies, the mortality rate tended to increase in HD patients without residual renal function, so such a schedule should be attempted while sufficiently watching changes in the patients' residual renal function [34][35][36].…”
Section: ■ Summary Of Evidencementioning
confidence: 97%